Exceptionally uncommon overburden collapse behind a natural lava dam: Abandonment of the San-Rafael Waterfall in northeastern Ecuador. (October 2021) - Reyes, Pedro; Procel, Sandra; Sevilla, Jorge; Cabero, Ana; Orozco, Alexandra; Córdova, Jenry; Lima, Felipe; Vasconez, Francisco
Abstract: On February 2, 2020, a sudden collapse of the volcaniclastic debris avalanche deposit behind the natural lava-dam barrier of the San-Rafael waterfall, the highest of Ecuador before the collapse, changed the Coca River course through a stream bypass beneath the lava dam leading to both waterfall abandonment and rapid regressive erosion. An initially slow retreat process which occurred during the waterfall stage involved two concomitant mechanisms, a basal plunge-pool undermining and a vertical plunge-pool drilling, each of which acting on both the basal debris avalanche deposits and the overlaying solid lava body, respectively. The lava-dam failure process did not occur as expected, but instead an early overburden collapse of the debris avalanche sequence behind the lava dam took place through two consecutive process: undermining of a basal cavity beneath the lava dam followed by a gradual down-washing of matrix particles from the debris avalanche deposit. Thus, the newly formed sinkhole captured the Coca River discharge. A rapid knickpoint retreat occurred upstream from the collapsed sinkhole which in turn evolved into a deep, steep-sided canyon gorge carved into loose sediments of the debris avalanche deposit thereby creating new transient small waterfalls and rapids. Valley-side slopes and floodplain bottom elevations, upstream from waterfall point, were modified by regressive erosion and canyon gorge formation. Graphical abstract: Image 1 Highlights: San-Rafael waterfall, the highest of Ecuador, was abandoned following an uncommon non-failed lava dam process. Vertical plunge-pool drilling, and basal undercutting operated as two simultaneous waterfall-retreat mechanisms. Gradual down-washing process and basal undermining of the debris avalanche deposit led to a sinkhole collapse. Rapid knickpoint retreat in the upstream direction formed a canyon gorge carved into the debris avalanche deposit.